2019
DOI: 10.1136/rmdopen-2018-000850
|View full text |Cite
|
Sign up to set email alerts
|

MRI of skeletal muscles in patients with idiopathic inflammatory myopathies: characteristic findings and diagnostic performance in dermatomyositis

Abstract: ObjectiveTo define the characteristic findings on MRI of skeletal muscles in patients with dermatomyositis (DM) relative to those in patients with other idiopathic inflammatory myopathies (IIMs) and to assess their diagnostic performance in DM.MethodsThirty-six patients with DM, 17 patients with amyopathic DM, 19 patients with polymyositis and 16 patients with non-IIM classified by the 2017 European League Against Rheumatism/American College of Rheumatology criteria were included in this study. The following M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 33 publications
2
44
0
4
Order By: Relevance
“…In patients with established diagnosis MRI can help to determine whether clinical muscle weakness is based on chronic muscle damage or relapse of active disease [157] . The characteristic MRI findings in patients with DM are high signal intensities in subcutaneous tissue and fascial areas, peripheral distribution and honeycomb pattern [158] . There is no standardized protocol for evaluation of MRI in patients with myositis.…”
Section: Treatment In Dmmentioning
confidence: 99%
“…In patients with established diagnosis MRI can help to determine whether clinical muscle weakness is based on chronic muscle damage or relapse of active disease [157] . The characteristic MRI findings in patients with DM are high signal intensities in subcutaneous tissue and fascial areas, peripheral distribution and honeycomb pattern [158] . There is no standardized protocol for evaluation of MRI in patients with myositis.…”
Section: Treatment In Dmmentioning
confidence: 99%
“…In the myositis group, highest MRI scores were observed for muscle fatty replacement, followed by edema and CM uptake ( Figure 3 ). Gadolinium enhancement is reported to be mainly present in subcutaneous and fascial areas in inflammatory myopathies 5 as a form of myofasciitis. Our findings support the notion that edema and muscle fatty replacement are key findings in muscle MRI of patients with suspected myopathies.…”
Section: Discussionmentioning
confidence: 99%
“… 5 A specific MRI pattern has already been established for single neuromuscular disorders, for example, idiopathic inflammatory myopathies (IIMs), including dermatomyositis, polymyositis, and inclusion body myositis. 5 , 6 Muscle MRI is also helpful in genetically determined myopathies like facioscapulohumeral dystrophy (FSHD) 7 and other muscular dystrophies, 8 showing a specific pattern of affected muscles based on fat replacement recognizable on MRI. However, many of these patterns are overlapping 9 and critical to interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…The proximal legs are preferentially examined because thigh muscles are mostly affected in IIM patients 12 . Although previous studies reported characteristic muscle MRI findings in IIM patients 11 16 , quantitative or semi-quantitative assessments with MRI have been limited 12 .…”
Section: Introductionmentioning
confidence: 98%